Bioglass®-based scaffolds incorporating polycaprolactone and chitosan coatings for controlled vancomycin delivery - Yao, Qingqing; Nooeaid, Patcharakamon; Roether, Judith; Dong, Yanining; Zhang, Qiqing; Boccaccini, Aldo R. (Ceramics International, 2013)
Highly porous scaffolds have been fabricated by the replication technique using 45S5 Bioglass® (BG) powder. For the purpose of imparting a local drug release capability, the scaffolds were coated with polycaprolactone and vancomycin-loaded chitosan by a two-step procedure. Bare BG scaffolds loaded with vancomycin via a direct immersion method were used as control. The chemical composition and microstructure of bare and coated scaffolds were characterized through Fourier-transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM), respectively. The mechanical properties of the coated scaffolds were significantly improved compared with uncoated scaffolds; the compressive strength values of the coated scaffolds were about 3 times and the area under the stress-strain curve was about 7 times higher than those of the uncoated scaffolds. The scaffolds degradation behavior and the drug release profiles were studied in a phosphate buffered saline (PBS) solution. There was a sharp release of the drug in the first few hours (8 h) for both bare and coated scaffolds. For the bare scaffolds the drug was released completely in 24 h. However, the coated scaffolds showed a sustained release in a period of 11 days, suggesting the potential of the present polymer coated BG scaffolds to be used as bone tissue scaffolds with drug carrier and delivery ability. © 2013 Elsevier Ltd and Techna Group S.r.l.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.biogla
Keywords: Bioactive glass; Drug delivery; Scaffolds; Tissue engineering